Towards Inclusive, Quality ICT-Based Learning for Rural Transformation - Chinapah, Vinayagum; Odero, Jared O. (Journal of Education and Research, 2016)
Information and communication technology (ICT) has emerged as a tool that can enhance flexible learning pathways. ICT has the potential to increase equitable access to quality learning, which is essential for skills development. Skills are required in technology-related nonfarm activities so as to improve livelihoods and achieve sustainable rural transformation. However, slow pace of the developing countries to utilize the benefits of the ongoing technological revolution in the North has resulted in the ‘digital divide’. Besides, it is still problematic to implement ICT programmes for educational development. The current and future challenges of providing ICT-based learning desperately call for the reengineering of education to move out of the formal structure of teaching and learning, towards building a more practical and realistic approach. By means of a literature review, this paper examines and discusses why it is important to provide inclusive, quality ICT-based learning, particularly in the rural areas of Asia and sub-Saharan Africa (SSA). It recommends that diverse ICT-based solutions be adopted to promote skills development and training within non-formal and informal settings. More comparative studies are also required to understand the impact of ICT-based learning in rural areas.